Повышение производительности котлов за счёт снятия ограничений мощности по тяге и дутью - Арсирий, Василий Анатольевич; Смирнова, Валерия Александровна; Арсирий, Елена Александровна (НТУ "ХПИ", 2016)
На основе анализа параметров дутьевых трактов и режимов работы вентиляторов предложен вариант снятия ограничений тепловой мощности котельных установок марки КВГМ (котел водогрейный, газомазутный) по дутью за счёт корректировки аэродинамики во входном патрубке вентилятора и вспомогательных элементах дутьевого тракта типа "поворот". Предлагаемый вариант снятия ограничений тепловой мощности является энергосберегающим потому, что позволяет существенно увеличить подачу воздуха в котельную установку с одновременным снижением затрат мощности на привод вентилятора.

A new highly informative method of ″flow structure visual diagnostic″, which allows you to identify the distribution of flow velocities actual values in flow parts. Solving problems experience in flow parts improving showed that today to analyze the efficiency it's uses only the effectiveness measure of the basic elements – pumps or fans, and the hydraulic resistance meanings in the equipment flow parts. To analyze of the flow structure improving results it was developed the effectiveness measure of equipment in general and its individual elements, and it was developed the system effectiveness measure for hydraulic and aerodynamic systems. Visual diagnostics gives us the opportunity to develop a new energy-saving technology, which allows to improve existing equipment, or to design the new one.
Increasing productivity of the boiler by eliminate the limited capacity of the thrust and blow
Keywords: котельные установки; вентиляторы; гидравлические сопротивления; визуализация структуры потоков; hydraulic resistance; visualization of flow structure